Plant components and soil organic matter - Paul, Eldor A., author; Appleton Century Crofts, publisher (Colorado State University. Libraries, 1970)
Large amounts of cellulose, aromatics, and proteinaceous compounds are introduced into the geochemical carbon pool as products of biological activity, or by economic and public health endeavors. Industrial wastes, pesticides, and detergents belong to the latter category. A net dry matter production of 1 kg/m2, representing about 4000 k. cal of energy, is attained in a significant portion of temperate terrestrial ecosystems (MacFayden, 1967). Most of the annual net primary productivity falls to the surface of the soil or is present as roots and is decomposed there. It is not surprising, therefore, that nearly every naturally produced organic compound can be isolated from the soil in at least small concentrations. The ability of multicellular plants and animals to cleave the aromatic ring appears to be restricted, most phenolics merely being modified by these organisms which do not seem to contribute substantially to the cyclization of aromatic carbon. Microorganisms, alone and in association with the soil fauna, bear the burden of releasing this carbon. Soil, being the major geostation in the cycling of terrestrial elements, is the site of greatest activity (Towers, 1964; Odum et al., 1967).Plant and animal residues with an adequate content of nutrients and a fairly low lignin content are rapidly degraded. The rate of decomposition is dependent on the moisture content, aeration, and temperature of the soil. It is only under conditions such as anaerobiosis, peat formation, or the initial colonization of a denuded landscape that plant carbon accumulates faster than it is decomposed (Ghilarov, 1967). In other environments, decomposition more or less balances the primary productivity of the higher plants and algae (Delwiche, 1965; Kononova, 1966; Burges, 1967). The contribution of plant residues and soil humus to plant growth, soil productivity, and genesis is well recognized (Russell, 1961; Tisdale and Nelson, 1966). Energy flow through producers, consumers, and decomposers is being stressed in ecosystem research (ICSU, 1967). This, plus the questions concerning the geocycle of nutrients in nature (Delwiche, 1965) and the detoxification of environmental pollutants (Breth and Stelly, 1966), makes it imperative that information be obtained relative to the turnover rate of plant constituents, and the recalcitrant humic components in soil. In this review, no attempt has been made to cover the extensive organic matter literature. The characterization of plant and soil components relative to their turnover in nature has been stressed.
Keywords: soil organic sulfur; nitrogen component; soil organic matter; soil humic compounds